MODEL COLD CHAIN MANAGEMENT OF BEEF IN INDONESIA: A BUSINESS PROCESS - Resista Vikaliana (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
This paper aims to study the results of research related to cold chain management of beef in Indonesia. The methodology used is literature study with descriptive research type analysis. In this study recommended cold chain and cold storage are one of the most important elements to help improve the quality of meat distribution throughout Indonesia. To create an effective and competitive cold chain, the role of all stakeholders is required. Beef Cold Chain Management in Indonesia is expected to effectively meet the needs of protein, especially beef throughout Indonesia at affordable prices society.